Endovascular Treatment of Intracranial Aneurysms in Patients 65 Years or Older: Clinical Outcomes - Gizewski, E.R.; Göricke, S.; Wolf, A.; Schoch, B.; Stolke, D.; Forsting, M.; Wanke, I. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: A controversial discussion concerning treatment of aneurysms in elderly patients exists. The aim of this study was to analyze clinical outcome in patients older than 65 years harboring intracranial aneurysms after endovascular treatment.MATERIALS AND METHODS: A total of 108 patients aged 65 years or older (mean age, 72 years, range, 65–87 years) were selected for endovascular treatment between 1997 and 2005. A total of 85 (78.7%) patients had an acute subarachnoid hemorrhage (SAH). SAH was classified according to Hunt and Hess (HH) grade: I (n = 16), II (n = 11), III (n = 33), IV (n = 19), and V (n = 6). There were 69 aneurysms that were small; 46, medium; 8, large; and 5, giant. Occlusion rate was categorized as complete (100%), subtotal (95% to 99%), and incomplete (<95%) obliteration according to the Raymond scale.RESULTS: Endovascular treatment was technically feasible in 108 of 113 aneurysms. Complete occlusion could be achieved in 80 patients; basal remnant was seen in 26 patients and a dog ear in 2 patients. Procedural complications included thrombotic vessel occlusion (n = 9), aneurysmal rupture (n = 4), and stenosis of the parent vessel (n = 2). The Glasgow Outcome Scale (GOS) for the patients with SAH after 6 months was good recovery (n = 43), moderate disability (n = 12), severe disability (n = 28), persistent vegetative state (n = 5), and death (n = 18). Outcome for the patients with unruptured aneurysms was good recovery in all 23 patients. On follow-up digital subtraction angiography (DSA) in 69 patients, complete aneurysmal occlusion was confirmed in 81% after 6 months. Five patients with recanalization were re-treated with coiling.CONCLUSION: Endovascular treatment of ruptured and unruptured intracranial aneurysms in this subgroup was safe and effective.